Establishing a standard protocol for the voiding cystourethrography. Issue 6 (December 2016) - Frimberger, Dominic; Bauer, Stuart B.; Cain, Mark P.; Greenfield, Saul P.; Kirsch, Andrew J.; Ramji, Faridali; Mercado-Deane, Maria-Gisela; Cooper, Christoper S.
Summary: The voiding cystourethrogram (VCUG) is a frequently performed test to diagnose a variety of urologic conditions, such as vesicoureteral reflux (VUR). The test results determine whether continued observation or an interventional procedure is indicated. VCUGs are ordered by many specialists and primary care providers, including pediatricians, family practitioners, nephrologists, hospitalists, emergency room physicians, and urologists. Current protocols for performing and interpreting a VCUG are based on the International Reflux Study in 1985. However, more recent information provided by many national and international institutions suggests a need to refine those recommendations. The lead author of the 1985 study, R.L. Lebowitz, agreed to and participated in the current protocol. In addition, a recent survey directed to the chairpersons of pediatric radiology of 65 children's hospitals throughout the United States and Canada showed that VCUG protocols vary substantially. Recent guidelines from the American Academy of Pediatrics (AAP) recommend a VCUG for children between 2 and 24 months of age with urinary tract infections but did not specify how this test should be performed. To improve patient safety and to standardize the data obtained when a VCUG is performed, the AAP Section on Radiology and the AAP Section on Urology initiated the current VCUG protocol to create a consensus on how to perform this test.